2017
DOI: 10.4103/1658-354x.197337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal clonidine and fentanyl in hyperbaric bupivacaine for spinal anesthesia and postoperative analgesia in patients undergoing lower abdominal surgeries

Abstract: Background:There are many adjuvant used along with bupivacaine for subarachnoid block, but fentanyl and clonidine are commonly used as adjuvant to intrathecal bupivacaine for prolonging both sensory and motor blockade as well as postoperative analgesia in patients undergoing lower abdominal surgeries.Objective:There is a paucity of studies comparing the efficacy of fentanyl and clonidine as adjuvant to intrathecal bupivacaine for improving intraoperative effect and postoperative analgesia in lower abdominal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Duration of analgesia was significantly prolonged in clonidine group (502.45±120.84 min) than in fentanyl group (401± 100.70 min), (P < 0.05). These results were in accordance with the study conducted by Shidhaye RVet al 15 and Bajwa BS et al 16 where they found prolonged analgesia in clonidine group as compared to fentanyl group. The increase in duration of post operative analgesia, seen with fentanyl and clonidine in our study, was different from some of the previous studies [3][4][5]13,14 and that may be due to difference in doses of clonidine, fentanyl, or bupivacaine used in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Duration of analgesia was significantly prolonged in clonidine group (502.45±120.84 min) than in fentanyl group (401± 100.70 min), (P < 0.05). These results were in accordance with the study conducted by Shidhaye RVet al 15 and Bajwa BS et al 16 where they found prolonged analgesia in clonidine group as compared to fentanyl group. The increase in duration of post operative analgesia, seen with fentanyl and clonidine in our study, was different from some of the previous studies [3][4][5]13,14 and that may be due to difference in doses of clonidine, fentanyl, or bupivacaine used in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Literature is divided regarding efficacy of both intrathecal clonidine and fentanyl in providing prolonged postoperative analgesia. Studies by Khezri et al .,[ 7 ] Bajwa et al .,[ 8 ] Chhabra et al .,[ 9 ] and Sharan et al . [ 10 ] opined that intrathecal clonidine was more potent in providing prolonged analgesia compared to intrathecal fentanyl.…”
Section: Introductionmentioning
confidence: 99%
“…for the persistence of postoperative analgesic time. [16,17] It was also supported by other different studies which gave the evidence of 50 µg clonidine to intrathecal bupivacaine made the lengthening of analgesic duration in comparison to 25 µg fentanyl with bupivacaine [18][19][20].…”
Section: Discussionmentioning
confidence: 72%